Household Health Expenditure in Thailand - สมใจ ดรุณวรรณ (Journal of Health Science of Thailand, 2011)
This paper attempts to explain household health expenditure that is the largest shares of the Healthcare expenditure. Increasing of household health expenditure is very interesting in determinants of a household total healthcare consumption. Consumption of healthcare can be explained by 3 concepts: demand for health, demand for health services and need for health services that can be used to predict household health expenditure. Moreover, these concepts can be used to plan for controlling household health expenditure and improving the efficiency of utilizing health resources in the future.